Efektifitas Ceramah terhadap Pengetahuan Kader Kesehatan tentang Penyakit Talasemia di Kecamatan Pekuncen dan Kecamatan Sumbang Kabupaten Banyumas - SR, Dwi Sarwani; Nurhayati, Nunung; Supriyanto, . (Universitas Ahmad Dahlan, 2014)
ABSTRACTBackground: One of the causes of the ineffective preventing of Thalassemia and getting more cases in Pekuncen and Sumbang sub district Banyumas was inadequate knowledge of the disease. Health volunteers had an important role to the distribution of information about thalassemia to the people. This research was aimed to observe the effectiveness of lecture method in improving knowledge of health volunteers on Thalassemia in Sumbang and Pekuncen sub district.Methods: The researcher applied quasi experiment through pretest and posttest design in her research. The population covered the active health volunteers in Sumbang and Pekuncen Sub districts consisted of 64 people who met the criteria. For analyzing the data, the researcher used univariate and bivariate (Wilcoxon test).Results and conclusion: The research showed that there was a different knowledge before and after lecture activity, the average score of knowledge before getting the treatment was 10.82 and it improved into 12.18 after the lecture session. There was 60.7% volunteers that was improved their knowledge after obtaining lecture session on thalassemia.Keywords: thalassemia, health volunteer, lecture method